2014
DOI: 10.1212/wnl.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Moesin is a possible target molecule for cytomegalovirus-related Guillain-Barré syndrome

Abstract: This study provides Class II evidence that levels of serum anti-moesin antibodies accurately distinguishes CMV-related AIDP from non-CMV-related AIDP (sensitivity 83%, specificity 93%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 10 publications
0
39
1
Order By: Relevance
“…Anti-moesin IgG was not detected in five patients who had CMV infection but not GBS [26], which is in contrast to detecting anti-GM2 IgM antibodies in six of 10 (60 %) patients who had CMV infection but not GBS [10]. Although the findings by Sawai et al [26] should be validated by other investigators [27], it would be reasonable to consider that IgG antibodies, rather than IgM antibodies, are the effector molecules responsible for the development of CMV, as well as C. jejuni-related GBS and its variants.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Anti-moesin IgG was not detected in five patients who had CMV infection but not GBS [26], which is in contrast to detecting anti-GM2 IgM antibodies in six of 10 (60 %) patients who had CMV infection but not GBS [10]. Although the findings by Sawai et al [26] should be validated by other investigators [27], it would be reasonable to consider that IgG antibodies, rather than IgM antibodies, are the effector molecules responsible for the development of CMV, as well as C. jejuni-related GBS and its variants.…”
Section: Discussionmentioning
confidence: 83%
“…Sawai et al [26] recently identified membraneorganizing extension spike protein (moesin), which is expressed in the Schwann cell processes at the nodes of Ranvier, and is crucial for myelination as a target protein for serum IgG in CMV-associated GBS. Anti-moesin IgG antibodies were detected in five (83 %) of six patients with demyelinating GBS after CMV infection, and the antibody titer decrease was confirmed using paired samples [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highresolution immunocytochemistry of autopsy specimens in early stage AIDP showed complement activation marker C3d and terminal complement complex neoantigen C5b-9 along the outer surface of Schwann cells, associated with demyelination [13]. Recently, moesin has been implicated to be a target antigen for CMV related AIDP [14]. Given the proposed pathogenesis, the rarity of CMVassociated GBS in SOT patients might be due to their immunosuppressed state.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results showed that infection leads to antibody production, which cross-reacts with gangliosides and other glycolipids leading to myelin destruction by complement activation or by antibodies targeting macrophages via the Fc receptor and leading to both demyelination and nerve conduction failure [2, 14]. Furthermore, recent results point at pathogen-derived proteins as triggers of molecular mimicry involved in the GBS [1517]. …”
Section: Introductionmentioning
confidence: 99%